Pengaruh Motivasi, Iklim Organisasi, dan Kompensasi Terhadap Komitmen Organisasional : Studi di PT SCG Pipe And Precast Indonesia - Joko Ariawan (Warta Pendidikan | e-Journal, 2020)
Commitment predicted as a factor or suspected to influence the non-optimal performance of employees of PT. SCG Pipe and Precast Indonesia, which causes employee commitment to decline, and researchers want to know more about what factors can influence employee commitment, which researchers limit to motivational factors, work climate and compensation. Sample collection method using simple random sampling technique. This research was conducted using primary data. The sample of this study is employees who work at PT. SCG Pipe and Precast Indonesia. Sampling using nonprobability technique is saturated sample or often called total sampling because the number of employees is 65 people. This research was carried out quantitatively with multiple linear regression analysis method, by testing the statistical test hypothesist. The results showed that 88.9% organizational commitment was influenced by the variables Motivation, Organizational Climate, and Compensation variables. As for the rest (100% - 88.9%) which is 11.1% Organizational commitment is influenced by other factors outside of this research such as leadership, career paths and training and development. Motivation, Organizational Climate, and compensation simultaneously have a significant effect on organizational commitment of PT. SCG Pipe and Precast Indonesia. This means that the higher the motivation, the more conducive the organizational climate and the better the compensation of the company, the higher the organizational commitment of employees towards the company.